Public Organizations of Ukraine in the System of Preventing and Counteracting Domestic Violence (Law and Safety, 2020)
The problem of domestic violence that exists in Ukraine is recognized as a serious problem and requires significant and comprehensive efforts to its solution, as well as the involvement of various actors, whose activities are aimed at overcoming domestic violence. Public organizations play an important role in such activities, the role of which is reflected in the Law of Ukraine “On Prevention and Counteraction to Domestic Violence”. The scientific novelty of the article is to study the directions and forms of work of public organizations in the field of prevention and counteraction to domestic violence and their systematization, introduction into scientific circulation of analytical materials and information prepared by public organizations. The research methodology is based on a dialectical approach to the cognition of socio-legal phenomena through comparative and legal analysis of definitions, historical and analytical methods in studying the activities of public organizations and their participation in the formation and implementation of public policy, using the observation method.Analysis of the work of public organizations as subjects of state policy to prevent and combat domestic violence provided grounds to clarify the systematization of the main areas of such work. Such grounds include prevention of domestic violence, advocacy of ratification of the Istanbul Convention, advocacy, participation in public policy (development of programs at the national and regional levels), work with offenders, training of specialists, policy monitoring and provision of services to victims. Forms of work of public organizations develop in time and space, in accordance with the needs of practical activities. Improving the efficiency of public organizations is seen in their networking, strengthening cooperation with scientific and educational institutions.